Resistance in Uncinula necator to Triazole Fungicides in South African Grapevines - Halleen, F.; Holz, G.; Pringle, K.L. (South African Journal of Enology and Viticulture, 2017)
The distribution of Uncinula necator variants resistant to triadimenol, penconazole and flusilazole were determined in vineyards with suspected resistance in the regions Tulbagh, Franschhoek, Stellenbosch, De Dooms, Riebeeck Kasteel and Paarl. The regional subpopulations had all been exposed to triadimefon or triadimenol prior to 1989, when these fungicides were phased out and other demethylation-inhibiting fungicides (DMls) were applied. The occurrence of resistant variants in the subpopulations was compared with those in a vineyard in the Ceres Karoo region, which was isolated by two mountain ranges from the viticultural regions and where triadimefon was used prior to 1989, then abandoned. No other DMls were applied. A discriminatory germ tube length was used as a criterion to distinguish between sensitive and tolerant conidia at a discriminatory fungicide dose of 0.3 μg/mL. All the populations showed reduced sensitivity to triadimenol. This finding indicated an earlier shift in triadimenol sensitivity in the subpopulations and showed that resistant variants are sufficiently competitive to become established in vineyards. Cross-resistance between the triazoles was indicated by the frequency at which resistant variants occurred in subpopulations. The Ceres Karoo population was at baseline sensitivity level for penconazole and flusilazole. However, the four populations (De Dooms, Franschhoek, Riebeeck Kasteel and Stellenbosch) which showed the highest shifts in sensitivity to triadimenol, also displayed a high level of reduced sensitivity to flusilazole. This was in spite of the fact that only the Stellenbosch population was regularly treated with flusilazole. The other three populations were predominantly exposed to penconazole. Reduced sensitivity to penconazole was furthermore most prevalent in the Paarl K, Paarl I, Riebeeck Kasteel and De Dooms populations. Of these populations, Paarl K and Paarl I received predominantly penconazole, whereas the other two populations were treated with a range of DMis. Penconazole EDso values for the Paarl K, Paarl I, Riebeeck Kasteel and De Dooms pathogen populations (which showed the highest shifts in sensitivity to this fungicide) were 0.908, 1.022, 1.253 and 1.942 μg/mL, respectively. In these populations, 53%, 38%, 71 % and 91 % of the conidia respectively belonged to the 1.0-3.0 μg/mL and higher resistant classes. Reduced sensitivity to flusilazole was most prevalent in the Stellenbosch, De Doorns, Riebeeck Kasteel and Franschhoek populations. Flusilazole EDso values for these populations were 1.580, 1.813, 2.143, 3.885 μg/mL, respectively, whereas 83%, 82%, 96% and 79% of the conidia respectively belonged to the 1.0-3.0 μg/mL and higher resistant classes. These findings suggest a differing sensitivity of the pathogen to the three triazole fungicides which indicate that resistance to DMis is a multigenic trait in U. necator.